Environmental & architectural phenomenology. Vol. 25, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2014)
Vol. 25, No. 3, Fall 2014 (includes “items of interest,” “anniversary issue introduction,” and essays by various authors).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals